Statins and the risk of cataract - E. K. Butina; E. V. Bochkareva; I. V. Kim (Кардиоваскулярная терапия и профилактика, 2019)
Statins are one of the most commonly prescribed classes of drugs for the cardiovascular disease prevention and the treatment of hyperlipidemia. In the literature there is information about the association of statin taking and higher cataract risk. At the same time, there are studies that describe the protective effect of statins on cataracts. Due to the fact that with age the risk cataract increases, as does the likelihood of prescribing statins, the problem of side effects with its use is of particular importance. Despite the conflicting results, many authors agree that there is no convincing reason for statin refuse, since the advantages in cardiovascular risk reducing far outweigh the cataract risk and the possible need for its surgical treatment. The study presents 2 systematic reviews and 3 meta-analyzes about association of statin intake and cataract risk or its surgical treatment, as well as studies carried out over the past 5 years.